Mechanical Strength of Synthetic Casting Tape for Application to Fracture Treatment of Farm Animals - Hara, S.; Kawamoto, Y.; Nuta, S.; Tomizawa, N. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
Compressive and torsional strength of cyclindrically formed synthetic casting tape for animals (Vetcast Plus™), composed of polyurethane-impregnated glass fibres, was investigated to determine its adequate application to fracture treatment of farm animals. After the completion of curing reaction, six-layered samples of the synthetic casting tape tolerated a compressive load of 6630 N (680 kgf). The sixlayered casting tape had also a torsional strength of 64 N · m. The compressive strength increased with time after the initiation of curing reaction. The time required for practical curing (achieving more than 60% of a final strength) was only 30 min, and that for complete curing 120 min. It was demonstrated that efficacious and safe fracture treatment of farm animals could be carried out using the synthetic casting tape for animals when a layer number appropriate to the total body weight of the patient animal was employed. The information obtained in this study is thought to be very useful in clinical practice.Mechanical strength of poly-urethane-impregnated synthetic casting tape was investigated to determine its adequate application to fracture treatment of farm animals. It was demonstrated that mechanical strength of cylindrically formed samples of the casting tape depended upon the layer number, and the six-layered sample tolerated a compressive load of 6630 N and a torsional load of 64 N · m when completely cured.
Keywords: Compressive strength; torsional strength; synthetic casting tape; plaster of paris bandage; farm animals